Pengaruh Disiplin Kerja dan Pengawasan terhadap Peningkatan Produktivitas Kerja Karyawan CV. Chantika Lestari Panyabungan - Sayuti, Ahmad; Nasution, Abdelina; Makhrani, Makhrani (PT. Riset Press International, 2023)
This research aims to determine and analyze the influence of work discipline and supervision on employee work productivity at CV. Chantika Lestari Panyabungan. This research uses quantitative methods with the main problem being whether work discipline and supervision have a positive and significant effect on increasing employee work productivity at CV. Chantika Lestari Connection. The population in this study was the entire number of CV employees. Chantika Lestari Panyabungan numbered 56 people and the results were analyzed using Multiple Linear Regression. The results of the research show that work discipline does not have a significant effect on employee work productivity, but the supervision carried out has a positive impact and has a significant effect on CV employee work productivity. Chantika Lestari Panyabungan.